The Effect of Internet Related Problems on the Sexting Behaviors of Juveniles - Ricketts, Melissa L. (American journal of criminal justice, 2015)
The purpose of the present study is to contribute to the gap in the literature by investigating the sexting behaviors of adolescents under the age of 18 and how these behaviors are related to internet related problems. Using data collected from high school students in a rural county in western North Carolina, results indicated that deviant peer association and Internet-related problems were in fact associated with sexting by juveniles.